Application Measurement Tools of Luxmeter and White Diode Laser as Alternative Methods in Distinguishing Oil Candles Based Mixed the Light Intensity - Bahirah, Anis; Rahmadi, Aji; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
Research about the application of Luxmeter measuring instrumental with white diode laser to distribute the light intensity in pure or candle-contaminated cooking oil. This research is conducted by varying the range, so the result of intensity value is acquired. The result of research shows that there are differences in the light intensity value of both pure and candle-contaminated cooking oil. The output of measuring instrument in this research shows a different number between pure cooking oil and candle-contaminated cooking oil. Based on the data analyzed, 5 cm range from the Luxmeter sensor is the most sensitive area. From the calculation, the value acquired is 273,1349 ± 0.06 Cd, that means if the reading value is more than that value, the oil is identified as candle-contaminated if less the oil is pure.